The ethnics of the layered cake: Kue Maksuba as a philosophy of character and pedagogy for generation Z - Marzulina, Lenny; Erlina, Dian; Holandyah, Muhamad; Herizal, Herizal; Zalifah Putri , Hikmah; Azzahra, Yerasyadwuni (Indonesian Research Journal in Education |IRJE|, 2026)
This study explores the cultural values embedded in Kue Maksuba, a traditional layered cake from Palembang, South Sumatra, and examines their potential application as character education resources for Generation Z. Using a qualitative single instrumental case study design, data were collected through in-depth interviews and participant observation involving eight adult women aged 35 to 65 years, conducted during Ramadan 1447H (February to March 2026) in their domestic production environments in Palembang. Five overarching themes emerged: cultural values as pedagogical resource, philosophical meanings of ingredients for character education, the intergenerational transmission gap and its conditions for repair, modernization challenges to cultural integrity, and preservation strategies for educational integration. Findings demonstrate that patience, perseverance, communal cooperation, and respect are structurally encoded in the Ramadan production process of Kue Maksuba and are enacted with particular intensity during this period of communal spiritual discipline. Adult practitioner informants unanimously identified declining engagement among younger generations as the most urgent challenge facing the tradition, and consistently identified, from their direct family and community experience, the conditions under which intergenerational transmission can be meaningfully restored. This study argues for the development of pedagogical modules grounded in the Ramadan production philosophy of Kue Maksuba as a foundation for Generation Z character education in Indonesian educational settings.